Csapatépítés a HR-menedzser és a pszichológus szemszögéből - Gulyás, László; Turcsányi, Enikő (Jelenkori Társadalmi és Gazdasági Folyamatok, 2008)
In this paper we study one part of team work's subject, and try to give the main viewspoints of selecting team members. One author of this paper is psychologist, the other one is HR-manager, both of them try to systematize the selections methods of team-members their point of view.